Analysis of Students Mathematical Critical Thinking Ability In One Variable Of Linear Equation Material - Bempah, Haryati Octaviani; Hulukuti, Evi (Universitas Mercu Buana Yogyakarta, 2022)
Critical thinking is one of the essential abilities for students which is a process to evaluate, choose, solve problems, and make decisions with rational reasons that can be accounted for. This research classified as an exploratory descriptive research with a qualitative approach that aims to analyze and describe students’ mathematical critical thinking ability in one variable linear equation material. The indicators used to describe students' mathematical critical thinking ability include problem identification abilities, analysis, synthesis, inference, and evaluation. The research subjects are students of class VII-1 of SMP Negeri 2 Gorontalo in the 2021/ 2022 academic year who had finished studying the material of linear equation in one variable. Data collection techniques consisted of observation, written tests and interviews to dig up information about students’ mathematical critical thinking ability. While the data analysis techniques include data reduction, display data, and conclusion / verification. Based on result of this research, students’ mathematical critical thinking ability in linear equation in one variable materials was classified a moderate. It is influenced by several factors, such as accuracy in problem identifying, mastery of the linear equation in one variable concepts, and the prerequisite material (initial ability), students’ tendency to rely on memorization, and motivation.